Design and Simulation of GaussianFSK Transmitter in UHF Band Using Direct Modulation of ΣΔ Modulator Fractional-N Synthesizer - Noori Hasan, Ali Mohammed (Al-Khwarizmi Engineering Journal, 2008)
This research involves design and simulation of GaussianFSK transmitter in UHF band using direct modulation of ΣΔ fractional-N synthesizer with the following specifications: Frequency range (869.9– 900.4) MHz, data rate 150kbps, channel spacing (500 kHz), Switching time 1 µs, & phase noise @10 kHz = -85dBc. New circuit techniques have been sought to allow increased integration of radio transmitters and receivers, along with new radio architectures that take advantage of such techniques. Characteristics such as low power operation, small size, and low cost have become the dominant design criteria by which these systems are judged. A direct modulation by ΣΔ fractional-N synthesizer is proposed in this research, because this approach provides the required characteristics such as low power. The Σ∆ modulator placed on digital phase-locked loop to control the fractional value of the frequency division ratio thereby eliminating spurious and allowing good phase noise performance. The modulation type of Gaussian FSK is used to obtain high spectral efficiency of modulated waveform. The applications of this transmitter in low cost wireless data transfer, security systems, RF remote controls and wireless metering.